Female characters in the fiction of Zhang Ailing and Li Bihua - Tan, Ming Swee (2014)
Zhang Ailing is an important writer in modern Chinese literature. She became famous in Shanghai during the forties because she wrote about women. She wrote about the different situations that could befall a woman due to the pressure of society and time period. Besides that, she also exposed the innermost feelings of a woman. Li Bihua is a female writer from Hong Kong. During the eighties, she started to get attention. Many of her works were adapted in films. Li Bihua liked to write about eccentric women. In her stories, most of the female characters had extraordinary grace. Despite the fact that both women came from different eras, their works had many similarities. They both lived in heritage modern cities. Their novels show several similar themes and characters. Li Bihua even wrote in a manner that was similar to Zhang Ailing's unique style. This thesis compares several of their works, mainly Zhang Ailing's "Farewell, My Concubine", "Red Rose, White Rose", "Lust, Caution", and Li Bihua's "Farewell My Concubine", "Green Snake" and "Flirtatious women", to highlight the similarities and differences between the two authors. Their works reflect the similarities and differences of a woman's opinions on self-identity, love, and marriage as well as a woman's standing in the patriarchy from different eras.